Performative politics and the cultures of Hinduism : public uses of religion in Western India - Raminder Kaur (Permanent Black ;, 2003)
The Ganapati utsava, a major festival of western India dedicated to the elephant-headed god, raises compelling questions about the interplay of religion, spectacle and cultural politics. In a book that spans a century of epochal history, Raminder Kaur considers how the public festival has been interwoven with everday lives as well as the making of modern Indian nation.